Growth and Productivity of Sweet Corn (Zea mays saccharate Strut) at Various Planting Distances and NPK Fertilizer in Peatlands - Maulidi Maulidi; Warganda Warganda (Universitas Tadulako, 2022)
Cultivation of cereals on peatlands has specific constraints. The use of fertilizers and planting methods is important in optimizing the growth and productivity of cereal crops, including sweet corn. This study aimed to analyze the need for NPK fertilizer based on the growth and yield of sweet corn plants at various planting spacings on peatlands in Rasau Jaya. The study was conducted on peatlands in Rasau Jaya 2, Kubu Raya District, for about 8 months. This study used a Split Plot Design with a randomized block design (RBD) as the basic statistical design. Spacing was determined as the main plot, which consisted of 3 levels: j1 (planting distance 75×25 cm), j2 (planting distance 75×40 cm) and j3 (planting distance 80×20 cm), with NPK fertilizer as subplots consisting of 3 levels: p1 (300 kg NPK/ha), p2 (400 kg NPK/ha), and p3 (500 kg NPK/ha). It was repeated 3 times for each combination. There were 5 plant samples as the unit of observation per plot. The study showed that plant spacing had a significant effect (α = 0.05) on the weight of the cobs without husks, the weight of the cobs with husks, the greenness of the leaves, the diameter of the cobs, length of the cobs, and weight of the cobs per plot. NPK fertilizer significantly affected root volume, leaf area, plant dry weight, and leaf greenness at =0.05; meanwhile, an interaction was found on the use of NPK fertilizer and plant spacing on the cob diameter. According to the results, sweet corn's best spacing for growth and productivity was 75×25 cm and 80×20 cm. The best dose of NPK fertilizer was 500 kg/ha or 125% of the recommended dose. Planting spacing of 75×40 cm + NPK fertilizer 400 kg or 100% of the recommended dose and spacing of 75×25 cm + NPK fertilizer 500 kg or 125% of the recommended dose were the best treatment on the diameter of the cob